Deeply Etched Inner-Cavity Pit Reflector - M. Dernaika; L. Caro; N. P. Kelly; J. K. Alexander; F. Dubois; P. E. Morrissey; F. H. Peters (IEEE Photonics Journal, 2017)
A deeply etched pit reflector is presented in this paper. The pit is not depth sensitive and has a comparable reflection and loss to a slot. Moreover, a two-section 750 ${μ }{\text {m}}$ laser cavity based on the pits is demonstrated. The laser achieved a side-mode suppression ratio of 40 dB, a linewidth of 280 KHz, and tuning across 40 nm.